INTEGRASI KARAKTER DAN HIGHER OTHER THINKING SKILL (HOTS) DALAM PEMBELAJARAN IPA SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI 25 PEKANBARU - Peronika Dewi; Evi Suryawati; Metty Susanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Action research had been conducted to increase the science learning outcomes of second year students of SMP 25 Pekanbaru by integrating the character and Higher Other Thinking Skill (HOTS) in the class VII3 of Junior High School 25 Pekanbaru year 2017/2018. This action research was conducted on March up to April 2018. The subject of this research was all students of class VII3 of Junior High School 25 Pekanbaru with 38 students consists of 21 boy and 17 girls. The parameter of this study was student learning outcomes consist of three aspects i.e. affective, psychomotor and cognitive. The result of this study showed that integrated character and HOTS could increase the science learning outcomes of second year students of Junior High School 25 Pekanbaru. On the affective aspect, students character increased from 2,82 with good category on phase I to be 3,24 with good category on phase II. Then, student skill outcomes of 68,03 with deficient category on phase I increased to be 82,33 with enough category on phase II. Meanwhile, on the aspect cognitive, the average permeability increased from 78,03% with enough category on phase I becoming 78,55% on phase II with student learning comprehensiveness outcomes of 68,42% with deficient category on phase I increased to be 86,48% with good category on phase II. According to study results, it could be concluded that integrated character and Higher Other Thinking Skill (HOTS) in science could increase students VII learning outcomes of Junior High School 25 Pekanbaru.Keywords: Learning Outcomes, HOTS, Character